1996
DOI: 10.1093/oxfordjournals.jbchem.a021397
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Histidine Residues of RCC1 Are Essential for Nucleotide Exchange on Ran

Abstract: Charged amino acid residues of human RCC1 were converted to alanine and mutants which were unable to complement tsBN2 cells (a temperature-sensitive rcc1- mutant of the hamster BHK21 cell line) were selected. These RCC1 mutants were analyzed for the ability to inhibit premature chromatin condensation by microinjection into tsBN2 cells, and their steady-state kinetic parameters for guanine nucleotide exchange reaction were measured. Examined RCC1 mutants were unstable in tsBN2 cells at the restrictive temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…RCC1 proteins contain seven tandem repeats of 50-60 amino acids termed RCC1 repeats. These tandem repeats form a seven blade propeller structure with one side binding to Ran for exchange activity and the other bound to chromatin (Azuma et al, 1996(Azuma et al, , 1999Renault et al, 1998). Surprisingly, none of the sequenced protozoa contain typical RCC1 proteins with seven tandem RCC1 domains.…”
Section: The Master Switch Ranmentioning
confidence: 99%
“…RCC1 proteins contain seven tandem repeats of 50-60 amino acids termed RCC1 repeats. These tandem repeats form a seven blade propeller structure with one side binding to Ran for exchange activity and the other bound to chromatin (Azuma et al, 1996(Azuma et al, , 1999Renault et al, 1998). Surprisingly, none of the sequenced protozoa contain typical RCC1 proteins with seven tandem RCC1 domains.…”
Section: The Master Switch Ranmentioning
confidence: 99%
“…The loops interacting with the small GTPase Ran are indicated with brackets [see Renault et al, 2001]. The position of the mutations in RPGR are shown below the consensus repeat, while RCC1 mutations in prp20 and pim1 yeast mutants [Renault et al, 1998;Amberg et al, 1993;Matynia et al, 1998] and mutations affecting catalytic activity created by site-directed mutagenesis in human RCC1 [Azuma et al, 1996] are shown above the repeat. Mutations affecting residues conserved across all RCC1 proteins are shown in black.…”
Section: Mutations and Alternative Splicingmentioning
confidence: 99%
“…Subsequent studies have shown that the loss of RCC1 function at different points in the cell cycle gives rise to different phenotypes. When cells are shifted to the restrictive temperature in the S-phase, the RCC1 mutation results in an interruption of DNA replication, PCC, and a premature mitosis (Nishimoto et al, 1978; ing protein, ran or TC4 in mammalian cells, spil in S. pombe, and GSP1 and GSP2 in S. cerevisiae (Bischoff and Ponstingl, 1991;Matsumoto and Beach, 1991;Coutavas et al, 1993;Saitoh and Dasso, 1995;Azuma et al, 1996). Both proteins are required for normal cell cycle regulation (Matsumoto and Beach, 1991;Sazer and Nurse, 1994).…”
Section: Introductionmentioning
confidence: 99%